Improving thyroid function monitoring in head and neck cancer patients: A quality improvement study. (28th November 2019) - Bhatt, Nupur; Taufique, Zahrah; Kamen, Emily; Wang, Binhuan; Concert, Catherine; Li, Zujun; Hu, Kenneth; Givi, Babak
Abstract : Objective: To investigate and improve compliance of thyroid function monitoring in head and neck cancer patients who received radiotherapy to the cervical region before and after instituting quality improvement interventions. Methods: Using the Plan, Do, Study, Act (PDSA) methodology, patients with head and neck malignancies who received radiotherapy to the cervical region from 2013–2015 were identified at a tertiary medical center. The status of the patients' thyroid monitoring and related characteristics were recorded. A quality improvement project was subsequently implemented by data sharing and providing feedback to practitioners involved in head and neck cancer care and creating a tracking database for all patients who received radiotherapy to the neck. After implementation of these interventions, data was collected on patients meeting the inclusion criteria from 2015–2017. Results: One hundred fifty‐six patients met criteria pre‐intervention and ninety‐eight patients met criteria post‐intervention. Compliance of thyroid monitoring went up from 34% to 80% after interventions ( P  < .0001). There was a significant increase in thyroid testing performed by radiation oncologists after interventions from 2% to 21%, while medical oncologists and otolaryngologists remained consistent in their compliance rates. Conclusion: It is possible to improve compliance with evidence‐based recommendations and improve the quality‐of‐care for head and neck cancer survivors through simple, cost effective interventions. Level of Evidence: 2 Laryngoscope, 130:E573–E579, 2020